2017
DOI: 10.1038/nm.4354
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of reactive astrocytes with type I collagen induces astrocytic scar formation through the integrin–N-cadherin pathway after spinal cord injury

Abstract: Central nervous system (CNS) injury transforms naive astrocytes into reactive astrocytes, which eventually become scar-forming astrocytes that can impair axonal regeneration and functional recovery. This sequential phenotypic change, known as reactive astrogliosis, has long been considered unidirectional and irreversible. However, we report here that reactive astrocytes isolated from injured spinal cord reverted in retrograde to naive astrocytes when transplanted into a naive spinal cord, whereas they formed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
355
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 377 publications
(383 citation statements)
references
References 62 publications
9
355
1
Order By: Relevance
“…In support of this theory, a recent study by Hara et al pharmacologically blocked integrin signaling 2 weeks after SCI, thereby attenuating astrocyte scar formation and improving locomotor performance 32 . However, Anderson et al ablated reactive astrocytes in chronic glial scars 5 weeks after SCI and found that it did not promote axonal growth 49 .…”
Section: Is the Glial Scar Inhibitory Or Beneficial To Regeneration?mentioning
confidence: 94%
See 3 more Smart Citations
“…In support of this theory, a recent study by Hara et al pharmacologically blocked integrin signaling 2 weeks after SCI, thereby attenuating astrocyte scar formation and improving locomotor performance 32 . However, Anderson et al ablated reactive astrocytes in chronic glial scars 5 weeks after SCI and found that it did not promote axonal growth 49 .…”
Section: Is the Glial Scar Inhibitory Or Beneficial To Regeneration?mentioning
confidence: 94%
“…While NG2-derived Schwann cells likely contribute to remyelination, albeit at low levels, the role of NG2-derived reactive astrocytes remains unclear. Because NG2-derived reactive astrocytes are a transient population that do not upregulate proteins expressed highly by scar-forming astrocytes (nestin and vimentin), it is possible that they resemble more ‘helpful’ reactive astrocytes 32 . Overall, NG2 glia participate in the formation and resolution of glial scars beyond serving simply as a reservoir for generating oligodendrocytes.…”
Section: Functional Diversity Of Glial Cells In the Injured Cnsmentioning
confidence: 99%
See 2 more Smart Citations
“…Astrocytes were isolated according to previous methods [25,26]. At 3d post SCI, rats from the Sham and SCI groups (n = 6) were sacrificed, and the T9-T11 segment of the ventral spinal cord was dissected from Sham rats while a 2-cm long ventral segment that included the rostral and caudal areas to the injury epicenter was removed from SCI rats.…”
Section: Astrocytes Isolationmentioning
confidence: 99%